Inner Asia: The language of song ((?) Cynthia Bassette Productions, Inc., 2008)
Follow nomadic life in Mongolia and drop in on a family in their tent-like ger, which is home to these "5-animal" people. Spend a day with herders in tiny Tuva, an independent state and member of the Russian Federation. See Lake Baikal in Siberia where the Buryat people, also Inner Asians, still use the language of throat singing.
Keywords: Nomads -- Inner Asia; Mongolia, Siberia, and Tuva